Suppression of Hepatic FLOT1 (Flotillin-1) by Type 2 Diabetes Mellitus Impairs the Disposal of Remnant Lipoproteins via Syndecan-1. Issue 1 (January 2018) - Chen, Keyang; Wu, Qingsi; Hu, Kongwang; Yang, Chengwei; Wu, Xiangdong; Cheung, Peter; Williams, Kevin Jon
Abstract : Objective—: Type 2 diabetes mellitus (T2DM) and the atherometabolic syndrome exhibit a deadly dyslipoproteinemia that arises in part from impaired hepatic disposal of C-TRLs (cholesterol- and triglyceride-rich remnant apoB [apolipoprotein B] lipoproteins). We previously identified syndecan-1 as a receptor for C-TRLs that directly mediates endocytosis via rafts, independent from coated pits. Caveolins and flotillins form rafts but facilitate distinct endocytotic pathways. We now investigated their participation in syndecan-1–mediated disposal of C-TRLs and their expression in T2DM liver. Approach and Results—: In cultured liver cells and nondiabetic murine livers, we found that syndecan-1 coimmunoprecipitates with FLOT1 (flotillin-1) but not with CAV1 (caveolin-1). Binding of C-TRLs to syndecan-1 on the surface of liver cells enhanced syndecan-1/FLOT1 association. The 2 molecules then trafficked together into the lysosomes, implying limited if any recycling back to the cell surface. The interaction requires the transmembrane/cytoplasmic region of syndecan-1 and the N-terminal hydrophobic domain of FLOT1. Knockdown of FLOT1 in cultured liver cells substantially inhibited syndecan-1 endocytosis. Livers from obese, T2DM KK A y mice exhibited 60% to 70% less FLOT1 protein and mRNA than in nondiabetic KK livers. An adenoviral construct to enhance hepatic expression of wild-type FLOT1 in T2DM mice normalized plasma triglycerides, whereas a mutant FLOT1 missing its N-terminal hydrophobic domain had no effect. Moreover, the adenoviral vector for wild-type FLOT1 lowered plasma triglyceride excursions and normalized retinyl excursions in T2DM KK A y mice after a corn oil gavage, without affecting postprandial production of C-TRLs. Conclusions—: FLOT1 is a novel participant in the disposal of harmful C-TRLs via syndecan-1. Low expression of FLOT1 in T2DM liver may contribute to metabolic dyslipoproteinemia. Abstract : Supplemental Digital Content is available in the text.